On well posed impulsive boundary value problems for p(t)-Laplacian's - Galewski, Marek; O'Regan, Donal (Mathematical Modelling and Analysis, 2013)
In this paper we investigate via variational methods and critical point theory the existence of solutions, uniqueness and continuous dependence on parameters to impulsive problems with a p(t)-Laplacian and Dirichlet boundary value conditions.